Analysis of The Dialogical Narration in The Story of Prophet Yusuf in The Quran - Ardiansyah, Ade Arip; Musthafa, Izzuddin; Hermawan, Acep (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2023)
This study aims to analyze the narrative structure in the story of Prophet Yusuf in the Quran, focusing on its dialogical elements. This research uses a qualitative approach; the study employs narrative analysis to explore how conversations contribute to the construction of the overall story. The following steps and strategies will be used in this research: (1) Text Collection: (2) Text Analysis (3) Literature Review (4) Conceptual Framework (5) Comparative Analysis (6) Interpretation and Conclusion (7) References: All sources used in this research will be listed in the reference list, including Qur'anic verses, scholarly literature, and other sources. By deeply understanding the dialogic narrative elements, the study aims to reveal the significance of conversation, its role in character development, and its impact on critical themes in the narrative. Employing Austin's speech act framework, specifically emphasizing imperative speech acts, the analysis centers on 29 instances identified in verses (9, 10, 12, 15). Additionally, a subset of seven imperative sentence structures, found in verses (29, 47, 88, 101), is explored to deepen understanding, emphasizing the locution component. The main findings show that dialog in this story is not just a conversation but also plays a role in building conflict, revealing character, and conveying important messages. This dialogic narrative analysis can provide deeper insights into how the story of Prophet Yusuf is presented in the Qur'Än and how dialog becomes an essential element in religious narratives. This research is relevant to understanding religious literature and Islamic wisdom and can provide valuable insights into studying sacred texts; this study highlights the critical role of dialogic narrative in depicting the story of Prophet Yusuf and presents a deeper understanding of religious narrative in the Qur'Än. However, limitations include the exclusive focus on imperative speech acts, overlooking potential nuances of other speech act types, and a lack of contextual considerations. Recommendations for further research include a more in-depth exploration of the cultural and linguistic context in the dialog, hoping to provide further insights into how the Quran uses dialog elements to convey messages and moral values. In addition, it is suggested that this research can be used as a foundation to develop a dialogic narrative model that can be applied to daily life stories and provide a better understanding of communicative aspects in the Islamic literary tradition.